Adopting the Magnetic Marketing Philosophy to Achieve Tourist Customer Loyalty: Insights from Travel and Tourism Companies - Rahman Fattah, Ahmed; khaleel Ibrahem, Noor; Edan Al khazraje, Mohammed (Iraqi Journal for Administrative Sciences, 2026)
This study aims to analyze the impact of the adoption of magnetic marketing philosophy in enhancing the loyalty of tourism client, through a field study conducted on a sample of 87 employees in a number of travel and tourism companies. Magnetic marketing philosophy is building sustainable attractions with customers by providing attractive content, interactive experiences, and values in line with modern customer aspirations, which stimulates customers to voluntary interaction with the brand and pursuit of its link. The study adopted an analytical descriptive approach, used the data collection tool, and the results were analyzed using the V.26 SPSS program to test the relationship between the study variables. The analytical model includes magnetic marketing as independent variables, and client tourism as a continued change. The results showed a positive relationship with a statistically significant impact between magnetic marketing and client's tourism, which emerged a "message" and "media" as the strongest influences. The results also revealed the importance of investing in creative content and digital interactive experiments to consolidate the relationship with customers and promote their loyalty. The search for travel and tourism